Status of 21st-Century Liberal Arts Education: Curriculum Reform in Japanese Universities and Evaluation by Society - Reiko Yamada (MDPI AG, 2024)
Ever since bachelor's competencies were introduced as a reference standard in Japan, many Japanese higher education institutions have been exploring and practicing liberal arts education for the 21st century. This study posits that incorporating new elements into university education has been a significant trend in liberal arts education for the 21st century. Building on the results of a comprehensive survey, primarily involving universities and industry, this study provides an in-depth analysis of how 21st-century liberal arts education is evaluated and expected by companies and others. A questionnaire survey was administered to universities regarding their provision of 21st-century liberal arts education and the status of reforms toward this education, and to companies and other members of society regarding their expectations and evaluation of 21st-century liberal arts education provided by universities, as well as the content they evaluate as learning outcomes for university students and the qualities and skills they consider when employing them. The findings from the survey of universities and companies indicate that the average scores for curriculum reform and establishment of new courses at universities and host companies are relatively low, as indicated by the relatively low average scores for keywords that companies place importance on. Undeniably, universities' efforts toward reform and the reality of such efforts should be conveyed to the public. Through dialogue with the industrial sector, we can understand the necessity of sharing and realizing openness to developing human resources through collaboration and innovation.